The Impact of Green Packaging and Green Product on Purchase Decisions of Lee Minerale Products with Environmental Awareness as an Intervening Variable - Wahyudin, Wahyudin; Soegeng, Irwin Sukrisno; Frimayasa, Agtovia (Sean Institute, 2025)
Increasing consumer awareness of environmental issues has driven companies to adopt sustainable strategies in product development. This study aims to explore the influence of Green Packaging and Green Product on the purchase decisions of Lee Minerale products, with Environmental Awareness as an intervening variable mediating the relationship. The research method employed is a quantitative approach using a questionnaire survey, with respondents being consumers of Lee Minerale. The sample size used consists of 100 respondents. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SmartPLS). The results of the outer model test indicate that all constructs meet the criteria for validity and reliability, with adequate loading factors, AVE, and Composite Reliability. The inner model results show that Green Product has a significant influence on both Purchase Decision and Environmental Awareness, while Green Packaging significantly influences Environmental Awareness but does not directly affect Purchase Decision. Furthermore, Environmental Awareness is proven to be a significant mediator that strengthens the influence of Green Packaging and Green Product on Purchase Decision. This study emphasizes the importance of integrating sustainability practices into marketing strategies to enhance consumer purchase decisions. As a practical implication, companies are advised to strengthen the communication of sustainability values to consumers in order to increase competitive advantage in the market.